'Good' or 'well calculated'? Effects of feedback on performance and self-concept of 5- to 7-year-old children in math. Issue 3 (16th March 2022) - Berner, Valérie-D.; Seitz-Stein, Katja; Segerer, Robin; Oesterlen, Eva; Niklas, Frank
Abstract: In this quasi-experimental study, we investigated whether basic arithmetic skills and mathematical self-concept of young children can be influenced by feedback during an interactive session in which a game was played. German 5- to 7-year-old children ( n = 79) played an adaption of the game House of Numbers six times, either in a specific or an unspecific feedback group, or they belonged to a passive control group. In a pre- and post-test design, children's mathematical performance and self-concept were assessed twice. The results show that playing the game and receiving any feedback led to significantly greater gains in the acquisition of basic arithmetic skills than being in the passive control group. Children in the specific feedback group showed greater benefits. Children in all groups displayed very high mathematical self-concepts at pre-test, which they maintained in the specific and control groups but not in the unspecific feedback group.